Preparation of single-layer titanium oxide nanosheet and application of single-layer titanium oxide nanosheet in photocatalytic water decomposition
By using hydrazine hydrate to assist the hydrothermal reaction, efficient and stable single-layer Ti0.91O2 nanosheets are prepared, which solves the problems of poor stability and low yield of nanosheets in traditional methods, and significantly improves the reactivity and activity of photocatalytic water splitting. Hydrogen production efficiency.
Patent Information
- Application Number
- CN202411473534.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-21
AI Technical Summary
The TiO2 two-dimensional nanosheets prepared by traditional ultrasonic peeling method have problems of poor stability and low yield, which limits their wide application in photocatalytic reactions.
Using the method of hydrazine hydrate assisted hydrothermal reaction, efficient and stable single-layer Ti0.91O2 nanosheets were prepared through protonation, ultrasound-assisted exfoliation and hydrazine hydrate-assisted hydrothermal reduction.
It improves the electron hole separation efficiency of single-layer Ti0.91O2 nanosheets, generates more hydroxyl radicals and superoxide radicals, significantly improves the reaction activity of photocatalytic water splitting, and the hydrogen production efficiency reaches 255 μmol·h-1 .
Smart Images

Figure CN119330394A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of photocatalytic materials, and specifically relates to a single-layer Ti 0.91 Preparation of O2 nanosheets and their application in hydrogen production from water splitting. Background Art
[0002] Developing sustainable clean energy is an effective way to solve the two thorny problems of energy crisis and environmental degradation in today's society. Hydrogen energy, as a new clean secondary energy source, has attracted widespread attention due to its high calorific value, abundant reserves, and convenient storage and transportation. Solar energy can directly decompose water through photocatalysis, providing an effective way to obtain hydrogen energy, and the preparation of high-efficiency and environmentally friendly photocatalysts is the core issue of solar photocatalytic water splitting to produce hydrogen. Therefore, the study of new photocatalysts is of great significance to alleviating energy crises and environmental problems and promoting sustainable development.
[0003] Titanium dioxide's non-toxic, abundant reserves, high stability and easy synthesis and other physical and chemical properties make it widely used in energy, environment and catalysis. However, the photogenerated electrons and holes in titanium dioxide are prone to recombination in the photocatalytic reaction, which limits the charge separation efficiency of titanium dioxide. In addition, titanium dioxide has fewer surface catalytic sites, resulting in poor photocatalytic activity. Ultra-thin two-dimensional nanomaterials have attracted widespread attention due to their excellent physics, optics, chemistry, huge specific surface area and unique structure. Two-dimensional Ti 0.91 O2 nanosheets have been widely used in the field of photocatalysis since their synthesis. Compared with traditional TiO2 photocatalysts, Ti 0.91 O2 nanosheets can significantly inhibit the recombination probability of electrons and holes, promote the migration rate of carriers, and thus improve the activity of photocatalytic reactions. However, it is difficult to obtain single-layer nanosheets using the traditional ultrasonic exfoliation method, and the prepared two-dimensional nanosheets have poor stability. After being stored for a period of time, they are easy to re-stack and transform into multi-layer nanosheets, which limits their wide application in photocatalytic reactions. Therefore, it is very important to develop an efficient and stable method for preparing single-layer nanosheets and improve the yield and stability of single-layer nanosheets. Summary of the invention
[0004] Aiming at the problems of poor stability and low yield of TiO2 two-dimensional nanosheets prepared by traditional ultrasonic exfoliation method, the present invention provides a method for preparing single-layer TiO2 by hydrothermal reaction assisted by hydrazine hydrate. 0.91 O2 nanosheets and their application in photocatalytic water splitting.
[0005] To achieve the above object, the present invention adopts the following technical solution: A single layer Ti 0.91 The preparation method of O2 nanosheets is to first prepare lepidocrocite-type cesium titanate, and then obtain a single-molecule layer of TiO2 nanosheets through protonation, ultrasound-assisted exfoliation and hydrazine hydrate-assisted hydrothermal reduction.0.91 O2 nanosheets; which specifically includes the following steps: 1) After grinding TiO2 and Cs2CO3 for 60 minutes, put them into a muffle furnace, heat them to 800℃, keep them warm for 20 hours, and grind them again for 60 minutes after cooling to room temperature, and then heat them to 800℃ and keep them warm for 20 hours to obtain lepidocrocite-type cesium titanate (Cs 0.67 Ti 1.83 O4); 2) The lepidocrocite-type cesium titanate prepared in step 1) is immersed in a hydrochloric acid solution and stirred at room temperature for 4 days (the hydrochloric acid solution is replaced once a day). The product is then centrifuged and washed with deionized water until it is neutral or weakly acidic to obtain a layered protonated titanate (H 0.67 Ti 1.83 O4·H2O); 3) The protonated titanate prepared in step 2) was mixed with tetrabutylammonium hydroxide (TBA) solution and then ultrasonically treated for 14 days. The obtained dispersion was centrifuged to obtain a colorless and transparent Ti 0.91 O2 nanosheet sol; 4) Ti obtained in step 3) 0.91 The O2 nanosheet sol was transferred to a polytetrafluoroethylene-lined high-pressure reactor, hydrazine hydrate was added and stirred for 10 minutes, and then the reactor was placed in a steel jacket and heated for hydrothermal reaction. After the reaction was completed, the monolayer Ti was obtained by washing and drying. 0.91 O2 nanosheets.
[0006] Furthermore, the molar ratio of TiO2 to Cs2CO3 used in step 1) is 5.3:1.
[0007] Furthermore, the concentration of the hydrochloric acid solution in step 2) is 1 mol·L -1 .
[0008] Furthermore, the volume concentration of the tetrabutylammonium hydroxide solution in step 3) is 2.57%.
[0009] Furthermore, in step 3), 25.7 mL of tetrabutylammonium hydroxide is used per gram of protonated titanate.
[0010] Furthermore, the centrifugal speed in step 3) is 7500 r / min -1 , time is 5 minutes.
[0011] Furthermore, the Ti used in step 4) 0.91 The volume ratio of O2 nanosheet sol to hydrazine hydrate is 20:1.
[0012] Furthermore, in step 4), the temperature of the hydrothermal reaction is 100° C. and the time is 600 min.
[0013] Furthermore, the temperature rise in the operation adopts programmed temperature rise, and the temperature rise program is 5°C / min.
[0014] The single layer Ti 0.91 O2 nanosheets loaded with precious metal Pt can be used as photocatalysts for the photocatalytic decomposition of water to produce hydrogen.
[0015] Furthermore, the noble metal Pt in the monolayer Ti 0.91 The loading amount of O2 on the nanosheets was 1 wt%.
[0016] Furthermore, the photocatalyst is specifically a single layer of Ti 0.91 O2 nanosheets are added to a hexahydrate chloroplatinic acid solution and stirred evenly, and then placed in a photoreactor. After the reactor is evacuated to a vacuum, the light is turned on for a reaction of 10 hours, and then the O2 nanosheets are washed and dried to obtain the product.
[0017] Furthermore, the photoreactor is a cylindrical jacketed reactor, and the built-in light source is a 125W high-pressure mercury lamp; during the reaction, condensed water is introduced into the jacket to control the temperature to 10 ° C.
[0018] The present invention uses hydrazine hydrate to assist in preparing a single-layer Ti 0.91 O2 nanosheets are due to the fact that hydrazine hydrate can be adsorbed on the nanosheets, making the nanosheets more negatively charged, promoting the insertion of TBA molecules into Ti in the hydrothermal reaction. 0.91 O2 interlayer, thus obtaining a single-layer nanosheet. At the same time, the added hydrazine hydrate can act as a sacrificial agent and stripping agent to regulate the Ti 0.91 The dimensions of the O2 nanosheets are then 0.91 Loading the precious metal Pt on O2 nanosheets can inhibit the recombination of photogenerated electrons and holes, broaden the light absorption range, make the surface of the synthesized nanosheets rich in hydroxyl radicals and superoxide radicals, and improve the reaction activity of photocatalytic water decomposition.
[0019] The significant advantages of the present invention are: The present invention provides a single-layer Ti 0.91 Preparation method of O2 nanosheets and application of them in water decomposition and hydrogen production after loading with precious metal Pt. The present invention uses hydrazine hydrate as a stripping auxiliary material to strip the two-dimensional material by hydrothermal method to obtain a single layer of Ti 0.91 O2 nanosheets have a higher electron-hole separation efficiency and can generate more hydroxyl radicals and superoxide radicals. Loading the precious metal Pt as a co-catalyst can inhibit the recombination of photogenerated electrons and holes in the reaction, broaden the light absorption range, and solve the problem of low activity of traditional photocatalysts for decomposing water to produce hydrogen. The single-layer Ti obtained by the present invention can be used to generate a large amount of hydroxyl radicals and superoxide radicals. 0.91 O2 nanosheets loaded with Pt can efficiently decompose water to produce hydrogen, with a hydrogen production efficiency of 255 μmol·h -1 . BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 X-ray diffraction (XRD) patterns of nanosheets prepared in Example 1 and Comparative Examples 1 and 2, wherein a is the sample in Comparative Example 1, b is the sample in Comparative Example 2, and c is the sample in Example 1.
[0021] Figure 2 The precursor Cs obtained in the process of preparing nanosheets in Example 1 0.67 Ti 1.83 O4 and H 0.67 Ti 1.83 Scanning electron microscope (SEM) image of O4·H2O, where a is Cs 0.67 Ti 1.83 O4, b is H 0.67 Ti 1.83 O4·H2O.
[0022] Figure 3 Transmission electron microscope (TEM) images of the nanosheets prepared in Example 1 and Comparative Example 2 and their selected area transmission electron microscope electron diffraction images, wherein a is the sample of Comparative Example 2 and b is the sample of Example 1.
[0023] Figure 4 The UV-visible absorption spectra of the nanosheets prepared in Example 1 and Comparative Example 2 are shown.
[0024] Figure 5 Atomic force microscope (AFM) images of nanosheets prepared in Example 1 and Comparative Example 2, wherein A and B are samples of Comparative Example 2 and Example 1 and their corresponding thicknesses, respectively.
[0025] Figure 6 Electron paramagnetic resonance (EPR) images of the nanosheets prepared in Example 1 and Comparative Example 2 under ultraviolet light irradiation, wherein a is the hydroxyl radical signal and b is the superoxide radical signal.
[0026] Figure 7 This is a comparison chart of the hydrogen production rates of the Pt-loaded nanosheets obtained in Example 2 and Comparative Example 3 in water after being irradiated with ultraviolet light for 5 hours. DETAILED DESCRIPTION
[0027] A single layer Ti 0.91 The preparation of O2 nanosheets loaded with Pt includes the following steps: 1) TiO2 and Cs2CO3 were ground in an agate mortar at a molar ratio of 5.3:1 for 60 minutes, then placed in a muffle furnace and heated to 800°C at a rate of 5°C / min for 20 hours. After cooling to room temperature, the mixture was ground again for 60 minutes, then heated to 800°C for 20 hours to obtain lepidocrocite-type cesium titanate (Cs 0.67 Ti1.83 O4); 2) The lepidocrocite-type cesium titanate prepared in step 1) was immersed in 1 mol·L -1 The product was centrifuged and washed with deionized water until it was neutral or weakly acidic to obtain a layered protonated titanate (H 0.67 Ti 1.83 O4·H2O); 3) 0.1 g of the protonated titanate prepared in step 2) was mixed with 100 mL of deionized water and 2.57 mL of tetrabutylammonium hydroxide (TBA), and then ultrasonically treated for 14 days. The resulting dispersion was heated at 7500 r·min. -1 After centrifugation for 5 minutes, a colorless and transparent Ti 0.91 O2 nanosheet sol; 4) 40 mL of Ti obtained in step 3) 0.91 The O2 nanosheet sol was transferred to a polytetrafluoroethylene-lined autoclave, 2 mL of hydrazine hydrate was added and stirred for 10 min, then the autoclave was placed in a steel jacket and heated to 100 °C at a rate of 5 °C / min for 600 min. After the reaction was completed, the monolayer Ti was obtained by washing and drying. 0.91 O2 nanosheets; 5) 50 mg of the single-layer Ti obtained in step 4) 0.91 The O2 nanosheets were placed in a photoreactor, and 5 mL of 8 wt% hexahydrate chloroplatinic acid solution was added and stirred to mix. After that, the reactor was evacuated to vacuum and the light was turned on for 10 h. After washing and drying, a single-layer Ti with 1% Pt was obtained. 0.91 O2 nanosheets.
[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. The described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The photoreactor used was a cylindrical jacketed reactor with a built-in 125W high-pressure mercury lamp as the light source. During the reaction, the temperature was controlled at 10 ° C.
[0030] Example 1 This embodiment provides a single-layer Ti 0.91 O2 nanosheets, which specifically include the following steps: Step 1: Weigh 40 g of TiO2 and Cs2CO3 with a molar ratio of 5.3:1, grind them in an agate mortar for 60 min, and then put them in a muffle furnace at 5 °C min-1 After heating to 800℃, keep it at this temperature for 20h, cool it to room temperature, grind it again for 60min, and then grind it at 5℃·min -1 The temperature was raised to 800°C and kept at this temperature for 20 hours to obtain lepidocrocite-type cesium titanate; Step 2: Weigh 10 g of lepidocrocite-type cesium titanate prepared in step 1 and add it to 1000 mL of 1 mol·L -1 The product was stirred at room temperature for 4 days, with the hydrochloric acid solution replaced every day. -1 Centrifuge for 5 min, wash with deionized water until neutral or weakly acidic, and dry to obtain layered protonated titanate; Step 3: Weigh 0.1 g of protonated titanate, mix with 100 mL of deionized water and 2.57 mL of analytical grade tetrabutylammonium hydroxide (TBA), and ultrasonically treat for 14 days to obtain a dispersion; Step 4: The dispersion was heated at 7500 r / min -1 Centrifuge for 5 minutes to obtain a nearly colorless and transparent Ti 0.91 O2 nanosheet sol; Step 5: Take 40 mL of nanosheet sol into a 100 mL polytetrafluoroethylene-lined reactor, add 2.00 mL of hydrazine hydrate, stir for 10 min, and let stand; Step 6: Place the reactor in a steel jacket, heat it to 100°C at a rate of 5°C / min, and keep it warm for 600 minutes. After the reaction is complete, wash and dry to obtain a single layer of Ti 0.91 O2 nanosheets.
[0031] Example 2 This embodiment provides a single-layer Ti loaded with precious metal Pt. 0.91 O2 nanosheets, which specifically include the following steps: Step 1: 50 mg of the single-layer Ti prepared in Example 1 0.91 The O2 nanosheets were placed in the photoreactor, and 90 mL of deionized water was added and stirred for 15 min; Step 2: Add 5 mL of 8 wt% hexahydrate chloroplatinic acid solution into the photoreactor, stir evenly with a magnetic stirrer, then use a mechanical pump to evacuate the reactor to vacuum, turn on the light to react for 10 h, wash and dry to obtain a single-layer Ti with 1% Pt loading. 0.91 O2 nanosheets.
[0032] Comparative Example 1 This comparative example provides a Ti prepared by conventional ultrasonic exfoliation. 0.91 O2 nanosheets, which specifically include the following steps: Step 1: Weigh 40 g of TiO2 and Cs2CO3 with a molar ratio of 5.3:1, put them into an agate mortar and grind them for 60 min, then put them into a muffle furnace and heat them to 800 °C at a rate of 5 °C / min, keep them warm for 20 h, cool them to room temperature, grind them again for 60 min, and then heat them at 5 °C / min -1 The temperature was raised to 800°C and kept for 20 hours to obtain lepidocrocite-type cesium titanate; Step 2: Weigh 10 g of the lepidocrocite-type cesium titanate obtained in step 1 and immerse it in 1000 mL of 1 mol·L -1 The product was stirred in a hydrochloric acid solution at room temperature for 4 days (the hydrochloric acid solution was changed every day), and then the product was heated at 7500 r·min -1 Centrifuge for 5 min, wash with deionized water until neutral or weakly acidic, and dry to obtain layered protonated titanate; Step 3: 0.1 g of the protonated titanate prepared in step 2 was mixed with 100 mL of deionized water and 2.57 mL of analytically pure tetrabutylammonium hydroxide (TBA), and then subjected to ultrasonic treatment for 14 days to obtain a dispersion; Step 4: The dispersion is heated at 7500 r / min -1 After centrifugation for 5 minutes, a colorless and transparent Ti 0.91 O2 nanosheet sol.
[0033] Comparative Example 2 This comparative example provides a Ti prepared by a simple hydrothermal reaction. 0.91 O2 nanosheets, which specifically include the following steps: Step 1: Weigh 40 g of TiO2 and Cs2CO3 with a molar ratio of 5.3:1, grind them in an agate mortar for 60 min, and then put them in a muffle furnace at 5 °C min -1 After heating to 800℃, keep the temperature for 20h, cool to room temperature, grind again for 60min, and then grind again at 5℃·min -1 After heating to 800°C and keeping the temperature for 20 hours, lepidocrocite-type cesium titanate is obtained; Step 2: Weigh 10 g of lepidocrocite-type cesium titanate prepared in step 1 and add it to 1000 mL of 1 mol·L -1 The product was stirred at room temperature for 4 days, with the hydrochloric acid solution replaced every day. -1 Centrifuge for 5 minutes, then wash with deionized water until neutral or weakly acidic, and dry to obtain layered protonated titanate; Step 3: Weigh 0.1 g of protonated titanate, mix with 100 mL of deionized water and 2.57 mL of analytical grade tetrabutylammonium hydroxide (TBA), and ultrasonically treat for 14 days to obtain a dispersion; Step 4: The dispersion was heated at 7500 r / min -1Centrifuge for 5 minutes to obtain a nearly colorless and transparent Ti 0.91 O2 nanosheet sol; Step 5: Take 40 mL of nanosheet sol in a 100 mL polytetrafluoroethylene-lined reactor, stir for 10 min, and let stand; Step 6: Place the reactor in a steel jacket, heat it to 100°C at a rate of 5°C / min, and keep it warm for 600 minutes. After the reaction is complete, wash and dry it to obtain a multilayer Ti 0.91 O2 nanosheets.
[0034] Comparative Example 3 This comparative example provides a multilayer Ti loaded with precious metal Pt. 0.91 O2 nanosheets, which specifically include the following steps: Step 1: 50 mg of the multilayer Ti synthesized in Comparative Example 2 0.91 The O2 nanosheets were placed in the photoreactor, and 90 mL of deionized water was added and stirred for 15 min; Step 2: Add 5 mL of 8 wt% hexahydrate chloroplatinic acid solution into the photoreactor, stir evenly with a magnetic stirrer, then use a mechanical pump to evacuate the reactor to vacuum, turn on the light to react for 10 h, wash and dry to obtain a multilayer Ti loaded with 1% Pt. 0.91 O2 nanosheets.
[0035] Figure 1 The XRD patterns of nanosheets prepared in Example 1 and Comparative Examples 1 and 2 are shown in the figure. As can be seen from the figure, in the XRD spectrum (a) of the sample of Comparative Example 1, 2θ=10° is the diffraction peak of the HTO (020) crystal plane of titanate, indicating that there is a large amount of protonated titanate after ultrasonic stripping, and no pure thin-layer nanosheets are obtained. There is a very wide diffraction peak between 15-35°. It is speculated that the formation of this wide diffraction peak may be due to the ultrasound in the preparation process of the nanosheet, which reduces the lateral size of the nanosheet. In the XRD spectrum (b) of the sample of Comparative Example 2, 2θ=25.28° and 48.049° are the (101) and (200) crystal planes of anatase, and there are characteristic peaks of HTO. The intensity of the three peaks is very weak, indicating that after simple hydrothermal treatment at 100°C, some nanosheets are re-stacked according to the structure of titanate, and some titanate is converted into anatase-type titanium dioxide, which leads to a significant weakening of the intensity of the wide diffraction peak. It can be seen from the XRD spectrum (c) of the sample in Example 1 that after adding hydrazine hydrate to assist the hydrothermal reaction, the characteristic peaks of titanic acid and anatase disappeared, leaving only a broad diffraction peak at 20°-37°. This may be because hydrazine hydrate hydrothermal treatment inserts more TBA molecules between the layers of titanic acid, causing the layer structure to disappear and obtaining a single-layer nanosheet.
[0036] Figure 2 The precursor Cs prepared in Example 1 0.67 Ti 1.83O4 and H 0.67 Ti 1.83 SEM image of O4·H2O. It can be clearly seen from the image that the precursor Cs 0.67 Ti 1.83 O4 and H 0.67 Ti 1.83 O4 layered structure, and after the lepidocrocite-type cesium titanate precursor is protonated, the interlayer spacing is widened and the stacking degree is reduced.
[0037] Figure 3 The TEM images and selected area TEM electron diffraction images of the nanosheets prepared in Example 1 and Comparative Example 2. As can be seen from the figure, this is because the nanosheets prepared in Comparative Example 2 are stacked layer by layer, with obvious lattice fringes, and its selected area electron diffraction image has obvious diffraction points (a). The single-layer nanosheet prepared in Example 1 is thinner, and the electron beam can penetrate the nanosheet, showing a translucent effect, and its selected area electron diffraction image has obvious diffraction rings (b).
[0038] Figure 4 The UV-visible absorption spectra (using VarianCary500 Scan UV-Vis spectrometer) of the nanosheets prepared in Example 1 and Comparative Example 2. As shown in the figure, the single-layer nanosheet is affected by the quantum size effect and exhibits strong absorption of ultraviolet light with a wavelength less than 300nm, with the light absorption peak at 266nm.
[0039] Figure 5 Atomic force microscope (AFM) images of nanosheets prepared in Example 1 and Comparative Example 2. As can be seen from the figure, the thickness of a single-layer nanosheet is 0.85 nm, which is consistent with the theoretical thickness of a single-layer structure. A multilayer nanosheet is composed of two to three layers stacked together, with a thickness of 2.4 nm.
[0040] Figure 6 Electromagnetic paramagnetic resonance spectra (using a Brucker ESR 300E electron paramagnetic resonance instrument and DMPO to capture free radicals) of the nanosheets prepared in Example 1 and Comparative Example 2. As can be seen from the figure, the hydroxyl radicals and superoxide radicals generated by the single-layer nanosheet synthesized in Example 1 are significantly higher than those of the multi-layer nanosheet prepared in Comparative Example 2, proving that the single-layer structure is conducive to the separation of photogenerated electrons and holes.
[0041] Water decomposition hydrogen production test, 20 mg of the prepared material was added to a photocatalytic water splitting reactor, and after adding 90 ml of deionized water and 1 ml of hydrazine hydrate as a sacrificial agent, it was stirred for 15 min to make it evenly dispersed. Then the system was evacuated to a vacuum, and a 125 W high-pressure mercury lamp was used to simulate visible light source irradiation for 5 h, and the hydrogen production was detected online by gas chromatography.
[0042] 1. The hydrogen production activity of the synthesized nanosheets was investigated when the amount of hydrazine hydrate used in step 5 and the hydrothermal temperature in step 6 of Example 1 were changed (other conditions remained unchanged). The results are shown in Table 1.
[0043] Table 1 Effect of synthesis conditions on the rate of hydrogen production from water decomposition of the obtained nanosheets
[0044] As shown in Table 1, the hydrogen production activity of the samples prepared by adding hydrazine hydrate was significantly improved, and the maximum improvement was achieved under 100 °C hydrothermal conditions, with the hydrogen production rate reaching 120 μmol·h -1 .
[0045] 2. Considering the hydrogen production activity of different materials prepared in the examples and comparative examples, the results are shown in Figure 7 And Table 2.
[0046] Table 2 Comparison of the efficiency of photocatalytic water decomposition and hydrogen production of different materials prepared in the examples and comparative examples
[0047] Depend on Figure 7 As can be seen from Table 2, single-layer Ti 0.91 The O2 nanosheets loaded with Pt have the highest hydrogen production activity, with a hydrogen production rate of up to 255 μ·mol·h -1 This also confirms that compared with multilayer and three-dimensional structured nanosheets, the single-layer Ti synthesized using hydrazine hydrate as a stripping agent and surface morphology control agent is 0.91 O2 nanosheets can significantly inhibit the recombination of electrons and holes and have excellent photocatalytic performance.
[0048] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A single layer Ti 0.91 The method for preparing O2 nanosheets is characterized in that: First, lepidocrocite-type cesium titanate was prepared, and then a single-layer Ti was obtained by protonation, ultrasound-assisted exfoliation, and hydrazine hydrate-assisted hydrothermal reduction. 0.91 O2 nanosheets.
2. The single-layer Ti according to claim 1 0.91 The method for preparing O2 nanosheets is characterized in that: The steps include: 1) After grinding TiO2 and Cs2CO3 for 60 minutes, put them into a muffle furnace, heat them to 800℃, keep them warm for 20 hours, cool them to room temperature, grind them again for 60 minutes, heat them to 800℃ and keep them warm for 20 hours to obtain lepidocrocite-type cesium titanate; 2) immersing the lepidocrocite-type cesium titanate obtained in step 1) in a hydrochloric acid solution, stirring at room temperature for 4 days, centrifuging the product, and washing with deionized water until it becomes neutral or weakly acidic to obtain a layered protonated titanate; 3) The protonated titanate prepared in step 2) was mixed with tetrabutylammonium hydroxide solution and then ultrasonically treated for 14 days. The obtained dispersion was centrifuged to obtain a colorless and transparent Ti 0.91 O2 nanosheet sol; 4) In step 3) the Ti 0.91 Hydrazine hydrate was added to the O2 nanosheet sol, stirred for 10 min, and then heated for hydrothermal reaction. After the reaction was completed, the monolayer Ti was obtained by washing and drying. 0.91 O2 nanosheets.
3. The single-layer Ti according to claim 2 0.91 The method for preparing O2 nanosheets is characterized in that: The molar ratio of TiO2 to Cs2CO3 used in step 1) is 5.3:
1.
4. The single-layer Ti according to claim 2 0.91 The method for preparing O2 nanosheets is characterized in that: The concentration of the hydrochloric acid solution in step 2) is 1 mol·L -1 .
5. The single-layer Ti according to claim 2 0.91 The method for preparing O2 nanosheets is characterized in that: The volume concentration of the tetrabutylammonium hydroxide solution in step 3) is 2.57%; its usage is calculated based on 25.7 mL of tetrabutylammonium hydroxide per gram of protonated titanate.
6. The single-layer Ti according to claim 2 0.91 The method for preparing O2 nanosheets is characterized in that: The centrifugal speed in step 3) is 7500 r / min -1 , time is 5 minutes.
7. The single-layer Ti according to claim 2 0.91 The preparation method of O2 nanosheets loaded with Pt is characterized in that: Step 4) Ti used 0.91 The volume ratio of O2 nanosheet sol to hydrazine hydrate is 20:
1.
8. The single-layer Ti according to claim 2 0.91 The preparation method of O2 nanosheets loaded with Pt is characterized in that: Step 4) The temperature of the hydrothermal reaction is 100°C and the time is 600 min.
9. A single layer Ti prepared by the method of claim 1 0.91 The application of O2 nanosheets in photocatalytic water decomposition to produce hydrogen is characterized by: The noble metal Pt is loaded on the single layer Ti 0.91 O2 nanosheets are used as photocatalysts for the photocatalytic decomposition of water to produce hydrogen.
10. The use according to claim 9, characterized in that: Precious metal Pt on single layer Ti 0.91 The loading amount of O2 on the nanosheets was 1 wt%.